What is a sustainable retirement village? Perceptions from Australian developers - Hu, Xin; Xia, B.; Skitmore, M.; Buys, L.; Hu, Y. (Elsevier, 2017)
Developers are key stakeholders in delivering sustainable retirement villages. Understanding the way they perceive sustainability is of great significance in shaping the provision of sustainable living environments in this industry. This study explores village developers’ perceptions of a sustainable living environment through a comprehensive content analysis of their online descriptions of sustainability features of their villages. Thirty-nine sustainability features were identified, with the most mentioned being “care and services provision and accessibility”, “social interaction”, “secure/safe living” and “independent living”. The social sustainability of the retirement village environment was highly valued by developers, with the majority of the sustainability features relating to this feature, while environmental sustainability was largely ignored. Although there is no significant difference between the private and not-for-profit village developers regarding the numbers of sustainability features mentioned, the private village developers value “social interaction” more while the not-for-profit village developers prioritize “independent living” and “care and services provision and accessibility” the most. The research leads to a better understanding of retirement village developers’ perceptions on a sustainable living environment, which further reveals the meaning of sustainable retirement villages in Australia. All these will ultimate benefit the development of the Australian retirement village industry in general.